2017
DOI: 10.1111/1556-4029.13673
|View full text |Cite
|
Sign up to set email alerts
|

Weapon Use in Korean Homicide: Differences Between Homicides Involving Sharp and Blunt Instruments

Abstract: On the basis of information regarding 276 homicides committed in South Korea between 1987 and 2008, we compared offenders' and victims' characteristics, injury locations, weapon-related behavior, and offending behavior between homicides involving sharp and blunt instruments. The victims of sharp-force homicide were much younger relative to those of blunt-force homicide. In addition, homicides involving blunt instruments were more likely to be committed by offenders who lived with the victims. Most sharp-force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…One could argue that the same factors are in effect in homicides with multiple stab wounds, but with increasing possibility of injuring other regions and organs as a result of relative movement of the victim and assailant. Numerous studies have found that injuries to the thorax, particularly the left front thorax, are the most common also in deaths with multiple stabs (10,11,(18)(19)(20)26). A study of survivors of assault by sharp force trauma also found that most injuries were to the victims left side adding weight to the argument of right handedness (27) being a factor to consider.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One could argue that the same factors are in effect in homicides with multiple stab wounds, but with increasing possibility of injuring other regions and organs as a result of relative movement of the victim and assailant. Numerous studies have found that injuries to the thorax, particularly the left front thorax, are the most common also in deaths with multiple stabs (10,11,(18)(19)(20)26). A study of survivors of assault by sharp force trauma also found that most injuries were to the victims left side adding weight to the argument of right handedness (27) being a factor to consider.…”
Section: Discussionmentioning
confidence: 99%
“…There was an average of 18.8 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) sharp force homicides per year. They exhibited a significant reduction of 0.29 homicides per year (linear regression: p < 0.01, F = 10.6, R 2 = 0.32) ( Figure S1).…”
Section: Sharp Force Homicidesmentioning
confidence: 99%
“…First, it may be that offenders who used sharp instruments might find it difficult to transport the victims’ bodies because the scene would be bloody and because it would be difficult to contain the victim's blood while transporting the body. Second, previous studies reported that the use of sharp versus blunt objects in homicides was highly associated with the closeness of the offender–victim relationship . The proportion of victims killed by a family member or acquaintance was higher in homicides involving blunt force than sharp force .…”
Section: Discussionmentioning
confidence: 93%
“…This might be due to the impulsiveness of such crimes, which are seldom premeditated, therefore the choice often falls on the most accessible instrument or weapon [ 2 , 3 , 37 ]. It has been postulated that the relationship between the offender and victim is strongly associated with the type of weapon chosen: blunt instruments seem to be used in a high proportion of homicides involving family members and to be strongly associated with an outburst of emotions in offenders [ 41 ], whereas in sharp-force homicides, the higher the number of injuries sustained by the victim, the closer the victim-offender relationship [ 41 , 42 ]. Forensic psychiatrists also suggest that the type of mental disorder of the perpetrator may influence the choice of the weapon [ 36 , 37 ], with depatterning of behavior, common in schizophrenics, leading to a random choice at the crime scene, whereas delirium or hallucinations may explain the choice of unusual or atypical weapons [ 36 ].…”
Section: Discussionmentioning
confidence: 99%